Penerapan Terapi Back Massage Terhadap Intensitas Nyeri Rematik Pada Lansia - Wijanarko Heru Pramono; Yunita Wulan Suci L (Poltekkes Kemenkes Jakarta III, 2019)
Descrepit is part of the process of growth and development. Humans do not suddenly grow old, but develop from babies, children, adults and eventually grow old. This is normal, with physical and behavioral changes. From this process can cause various diseases such as rheumatism, which will cause a feeling pain in the joints. One method to reduce joint pain, descrepit people can be given back massge therapy. The purpose of this case study is to compile a nursing care regimen and identify the benefits of back massage therapy in reducing joint pain in Panti Wreda Harapan Ibu Semarang. This researcher used the design form of the one group pretest posttest. The subjects of this study were two descrepit people, with criteria for having rheumatic disease with joint pain, not taking analgesic drugs, age 60-70 years, willing to be respondents. The results of the study showed that the two respondents obtained the results of client I and II. The application of back massage therapy had decreased pain with a percentage of 60.6% and 60% with a decrease in average of 4. It was concluded that back massage therapy can reduce joint pain in the descrepit.